POTENSI EKSTRAK DAUN CAMELLIA SINENSIS SEBAGAI UPAYA PREVENTIF TERHADAP SERANGAN ASMA - Angelica Riadi Alim (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2021)
Background: Asthma is a respiratory disease that has a high prevalence worldwide. One of the symptoms of asthma is an asthma attack, which is shortness of breath. These symptoms can be fatal if not treated properly. Methods: The caffeine content in Camellia sinensis leaves can function as a bronchodilator so that the use of C. sinensis leaf extract can be the right solution in preventing asthma attacks and reducing asthma mortality. Discussion: contains theories, research results and also the discussion according to the topic Conclusion: The use of Camellia sinensis leaf extract has the potential as a preventive measure against asthma attacks. Keywords: asthma, Camellia sinensis, caffeine